Museums and art therapy: A bibliometric analysis of the potential of museum art therapy - Wei, Zhizi; Zhong, Chaofang (Frontiers in Psychology, 2022)
In this paper, the current promotion of art therapy in museum development and the potential value of the combination of museum and art therapy on mental health are explored. Individuals who usually evade any treatment may experience art therapy in a museum setting as a release from their suppressed emotions. Furthermore, art therapy may enable them to discover how to express themselves, thereby reducing anxiety and promoting a sense of social belonging, which may be unattainable in other healing settings. Moreover, this literature review afforded us a preliminary understanding of issues in museum education and art therapy, which require further examination, including implications for China’s museum art therapy in practice and future research directions.